2021
DOI: 10.1177/20417314211019375
|View full text |Cite
|
Sign up to set email alerts
|

Induction of osteogenic differentiation of bone marrow stromal cells on 3D polyester-based scaffolds solely by subphysiological fluidic stimulation in a laminar flow bioreactor

Abstract: The fatal determination of bone marrow mesenchymal stem/stromal cells (BMSC) is closely associated with mechano-environmental factors in addition to biochemical clues. The aim of this study was to induce osteogenesis in the absence of chemical stimuli using a custom-designed laminar flow bioreactor. BMSC were seeded onto synthetic microporous scaffolds and subjected to the subphysiological level of fluid flow for up to 21 days. During the perfusion, cell proliferation was significantly inhibited. There were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 72 publications
1
30
1
Order By: Relevance
“…Here, we present experimental data of superior scaffold integration of hMSCs due to dynamic rather than static conditions, while computational simulation revealed a mean wall shear stress of 8.5 mPa. Previously, simulations on a similar bioreactor setup showed that intermittent shear stress ranging from 0 to 13.35 mPa was able to induce osteogenic differentiation of rat-derived bone marrow stem cells seeded on a synthetic copolymer scaffold with a comparable porosity to ours, but with higher permeability, in the absence of any chemical stimuli [ 63 ]. Notably, our results show that mechanical conditions vary slightly depending on the position considered, i.e., velocity is highest near the inlet and outlet and more homogenous in the middle, while pressure showed a gradient between the inlet and outlet.…”
Section: Discussionmentioning
confidence: 91%
“…Here, we present experimental data of superior scaffold integration of hMSCs due to dynamic rather than static conditions, while computational simulation revealed a mean wall shear stress of 8.5 mPa. Previously, simulations on a similar bioreactor setup showed that intermittent shear stress ranging from 0 to 13.35 mPa was able to induce osteogenic differentiation of rat-derived bone marrow stem cells seeded on a synthetic copolymer scaffold with a comparable porosity to ours, but with higher permeability, in the absence of any chemical stimuli [ 63 ]. Notably, our results show that mechanical conditions vary slightly depending on the position considered, i.e., velocity is highest near the inlet and outlet and more homogenous in the middle, while pressure showed a gradient between the inlet and outlet.…”
Section: Discussionmentioning
confidence: 91%
“…In another study, continuous medium flow with a mean shear stress equal to 8.5 mPa improved the proliferation of human BMDSCs and increased ECM production compared to control cells cultured in static conditions [78]. In turn, Yamada et al [79] showed that during the perfusion (shear stress distribution ranging from 0.20 mPa to 0.40 mPa), cell proliferation on polyester-based scaffolds was significantly inhibited. However, they observed increased expression of osteogenesis-related genes (RUNX2, ALP, SP7, BSP, OPN, and OCN) in the absence of chemical stimuli (i.e., the application of dexamethasone) compared to static culture.…”
Section: Perfusion Bioreactorsmentioning
confidence: 97%
“…Some studies suggested that residual SCAPs in the apical papilla surviving the infection may induce or at least be partially responsible for the mineralized tissue formation or repair shown in regenerative endodontic treatment [14] . Osteogenic preconditioning prior to transplantation was shown to enhance bone formation at the recipient sites [15,16]. Moreover, SCAPs can be used to reconstruct the spinal cord injury in animal model [17].…”
Section: Introductionmentioning
confidence: 99%